PENERAPAN TEKNIK RELAKSASI BENSON UNTUK MENURUNKAN DISMENORE PADA MAHASISWI KEPERAWATAN DI STIKES KESDAM IV/DIPONEGORO SEMARANG - Yuni Astuti M.Kep (JURNAL KEPERAWATAN SISTHANA, 2023)
Dysmenorrhea is a physical disorder in women who are menstruating in the form of abdominal pain/cramping disorders. Benson relaxation is the development of a deep breathing relaxation method involving the patient's belief factor that can create a calm environment so that it can help patients achieve higher health and well-being conditions. This study aims to describe and analyze the application of Benson's relaxation technique in reducing the pain scale of dysmenorrhea in nursing students. The type of research used is descriptive with a case study approach. The subjects used were 2 people with criteria, namely students of STIKES Kesdam IV/Diponegoro Semarang, female students with dysmenorrhea pain, and female students who were willing to be given Benson relaxation measures. Pain measurement using the Numerical Rating Scale (NRS). Benson's relaxation intervention was carried out for 3 consecutive days. The results of the analysis showed that subject I experienced a decrease in the pain scale from the results of a scale of 4 (moderate) to II (mild), subject II from a scale of 3 (mild) to 0 (no pain). The results of the case study concluded that there was a decrease in the pain scale in female students with dysmenorrhea pain. Benson relaxation is recommended as a nursing intervention in pain management in female students who experience dysmenorrhea pain because it can reduce the pain scale significantly and is easy to do